Stunting In Children In Rural Related To Socio-Economic Conditions Of Communities - farona, cecilia; firnawati, artika fristi; Habibi, Mustainul (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2022)
Abstract — Incidence of stunting arises as a result of long-lasting conditions such as frequent recurring illnesses due to poor hygiene and sanitation, behavior improper parenting, and poverty. Researching the incidence of stunting is very important because stunting has a significant long-term impact on children's health and development. Stunting occurs when a child experiences chronic malnutrition over a long period of time, especially in the first 1,000 days of life, from the womb to 2 years of age. The impact of stunting on children includes a decrease in cognitive abilities and intelligence, a decrease in general physical health, a decrease in future productivity: Stunting can affect the quality of life in the future and hinder a child's ability to contribute to society and the economy. Therefore, researching the incidence of stunting is important to understand the factors that cause stunting and find solutions to prevent it so that Indonesia can survive the golden generation. This research is an observational study using a cross sectional design, using 107 toddlers. Bivariate data analysis using Kai-Square Test. The results showed that some of the parents in the Toddler Stunting group had basic education as many as 104 respondents (92.86%), most of them had farmer jobs as many as 75 respondents (66.97%) and most of their income was below the regional drinking wage (<UMR) as many as 67 respondents (59.82%). The results of the bivariate study found that two variables (Education and Income) were significantly related to the incidence of stunting (p-value <0.05).